2023
DOI: 10.1111/vcp.13198
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a viscoelastic point‐of‐care coagulation monitor with thromboelastography in sick dogs with hemostatic abnormalities

Abstract: Background: Viscoelastic coagulation monitor (VCM-Vet) is a point-of-care device that has been used to characterize hemostatic abnormalities in sick pets but has not been validated in veterinary patients. Objectives:We aimed to compare VCM-Vet and thromboelastography (TEG) in sick dogs with suspected disorders of hemostasis.Methods: Duplicate VCM-Vet tests using untreated native blood performed concurrently on two VCM-Vet machines, and simultaneous TEG tests were performed (one citrated native (CN), and one ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 38 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…11 It should be noted, however, that a fibrinolysis artefact of unknown origin has been noted with the VCM Vet, suggesting that concern over hyperfibrinolysis should be re-confirmed with a repeated sample. 7 The lysis index, measured at 30 (LI30) and 45 (LI45) minutes following maximum clot firmness, is a calculated value derived from the relationship between amplitude and maximum clot firmness, demonstrating the percentage of remaining clot firmness. 8 The lysis index, therefore, is used to evaluate plasmin-mediated fibrinolysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 It should be noted, however, that a fibrinolysis artefact of unknown origin has been noted with the VCM Vet, suggesting that concern over hyperfibrinolysis should be re-confirmed with a repeated sample. 7 The lysis index, measured at 30 (LI30) and 45 (LI45) minutes following maximum clot firmness, is a calculated value derived from the relationship between amplitude and maximum clot firmness, demonstrating the percentage of remaining clot firmness. 8 The lysis index, therefore, is used to evaluate plasmin-mediated fibrinolysis.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the VCM Vet has not specifically been reported in the assessment of hyperfibrinolysis due to A. vasorum , although changes in the lysis index have been noted in healthy dogs during the perianaesthetic period, 10 and a recent retrospective study extensively evaluated fibrinolysis demonstrated by the VCM Vet in a variety of diseased patients 11 . It should be noted, however, that a fibrinolysis artefact of unknown origin has been noted with the VCM Vet, suggesting that concern over hyperfibrinolysis should be re‐confirmed with a repeated sample 7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation